Are ASEAN 5 Countries Suitable for Optimum Currency Area? Exchange Rate Approach - Riyanto, Feri Dwi (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2020)
The issue of currency unification among ASEAN countries is often the concern of researchers given the reactive conditions of ASEAN countries to the 1997/1998 crisis and the 2008 financial crisis. This study aims to analyze the impact of ASEAN currencies (rupiah, ringgit, Singapore dollar, baht and peso) against shocks in other ASEAN countries. The concept of this study uses an exchange rate approach based on (peg) the currencies of ASEAN countries with the US Dollar and Singapore Dollar. In addition, this research aims to analyze the symmetrical response of currencies to shocks to currencies of other countries. The research method approaches the short and long-term vector autoregression (VAR) model using the monthly real exchange rate variable data from 1990 - 2018.The results of the impulse response function show that the response of ASEAN countries' currencies (rupiah, ringgit, Singapore dollar, baht and peso) is more symmetric base (peg) currency with the Singapore dollar compared to the US dollar. Keywords: Single Currency, ASEAN 5 Countries, Optimum Currency Area, Exchange Rates JEL: C23; F31